Given, (x+y)/xy = 2 => (x+y)=2xy----(i)
(x-y)/xy = 6 => x-y=6xy-----(ii)
Adding equation (i) & (ii),
x+y+x-y = 2xy+6xy = 8xy
=> 2x=8xy => y=1/4
Putting the value of y in eqn (i) we get,
x+1/4=2x*(1/4) => x+1/4=x/2=> x/2=-1/4 => x=-1/2
SO by solving both the equations we get, x=-1/2, y=1/4
Here, *= Multiplication
I hope my answer helps. All the very best for your future endeavors!
Question : $\left(4 x^3 y-6 x^2 y^2+4 x y^3-y^4\right)$ can be expressed as:
Question : The third proportional of the following numbers $(x-y)^2, (x^2-y^2)^2$ is:
Question : The factors of $x^2+4 y^2+4 y-4 x y-2 x-8$ are:
Question : Simplify the given expression $\frac{(x^3-y^3)(x+y)}{x^2+x y+y^2}$.
Regular exam updates, QnA, Predictors, College Applications & E-books now on your Mobile